Emotion Classification Using Web Blog Corpora - Yang, Changhua; Lin, Kevin Hsin-Yih; Chen, Hsin-Hsi (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
In this paper, we investigate the emotion classification of web blog corpora using support vector machine (SVM) and conditional random field (CRF) machine learning techniques. The emotion classifiers are trained at the sentence level and applied to the document level. Our methods also determine an emotion category by taking the context of a sentence into account. Experiments show that CRF classifiers outperform SVM classifiers. When applying emotion classification to a blog at the document level, the emotion of the last sentence in a document plays an important role in determining the overall emotion.